Kointegrasi Bursa Saham di Pasar Modal Indonesia, Malaysia, dan Korea Selatan - I Putu Ajie Windu K Windu K (Fakultas Ekonomi Universitas Garut, 2018)
One important indicator of the development of the capital market can be seen from the value of the composite stock price index. The composite price index reflects the performance of all stocks listed in a particular country. The purpose of this study is to examine the relationship between the stock exchanges of countries in Asia which consist of the stock exchanges of Indonesia, Malaysia and South Korea because these three countries are the oldest emerging markets in Asia, but these three countries have had a significant impact on the financial crisis. 1997 and 2008. The data used is the period January 1995 to December 2015 with two research formulas, namely the first is to test whether the stock exchanges of Indonesia, Malaysia, and South Korea are integrated and the second is to test which stock exchange is the most dominant among them. these three countries. The results of this study show that there is a long-term relationship between the capital markets of Indonesia, Malaysia and South Korea which is stated in the results of the cointegration test.